Recent Progress in Synthesis of Glycerol Carbonate and Evaluation of Its Plasticizing Properties - de Caro, Pascale; Bandres, Matthieu; Urrutigoïty, Martine; Cecutti, Christine; Thiebaud-Roux, Sophie (Frontiers in Chemistry, 2019)
The state of art on the glycerol carbonate (GC) synthesis has been updated since the last published reviews in 2012, 2013 and 2016. Three types of reactions continue to be studied: glycerolysis of urea, transcarbonation of DMC, DEC or cyclic carbonates with glycerol and reaction using CO2. Among these different routes, DMC and glycerol were selected as the raw materials for the GC synthesis in this work since the transcarbonation from these green reagents leads to high yields and selectivities, using mild conditions including a less energy consuming GC separation process. Catalytic conditions using Na2CO3 seem to be a good compromise to achieve a high yield of GC, leading to an easier purification step without GC distillation. Mild temperatures for the reaction (73-78°C) as well as a low waste amount confirmed by the E-factor calculation, are in favor of controlled costs. Plasticizing properties of synthesized GC were compared to the behaviors of a commercial plasticizer and natural dialkyl carbonates, for a colorless nail polish formulation. The resulting films subjected to mechanical and thermal stresses (DMA and Persoz pendulum) showed the high plasticizing effect of GC towards nitrocellulose based films, probably due to hydrogen bond interactions between GC and nitrocellulose. The GC efficiency gives the possibility to decrease the content of the plasticizer in the formulation. Glycerol carbonate can be thus considered as a biobased ingredient abiding by the green chemistry concepts, and safe enough to be used in an ecodesigned nail polish formulation.